Enhancing Financial Literacy and Entrepreneurship Behavior Among Market Vendors: A Case Study of Kiko Market With Focus on Emyooga Program - Mellan Nambatya (Uganda Christian University, 2024)
The market vendors provide the informal economy of Uganda with necessary goods and services that help a large fraction of the population. A significant number of Ugandan market vendors have to experience struggles in business due to limited financial literacy and entrepreneurial skills. As noted by Musoke (2021), "an overwhelming percentage of the vendors" in Ugandan markets operate with a very basic understanding of financial management, hence curtailing their potential for saving, investment, and business expansion. This might lead to heightened vulnerability to predatory lending, a lack of access to formal credit, and mediocre growth in business. On the flip side, entrepreneurial behavior may unleash the power of opportunity identification, effective management of resources, and adaptability to changing market conditions among vendors.